Effects of BIM in Enhancing Prefabricated Construction - Sherra, Abdelrahman Mohamed Ezzat (2021)
A Master of Science thesis in Civil Engineering by Abdelrahman Mohamed Ezzat Sherra entitled, “Effects of BIM in Enhancing Prefabricated Construction”, submitted in December 2021. Thesis advisor is Dr. Irtishad Ahmad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).